Brittle: Re-thinking Narratives of Disordered Eating through Fanfiction - Neugarten, Julia (FRAME, Journal of Literary Studies, 2026)
This paper analyzes how Brittle (sammehsayum 2012), a popular work of fanfiction for the TV show Supernatural (2005-2020), relates to the Supernatural canon and to dominant cultural narratives on masculinity and eating disorders as identified by Bordo (1993) and Contois (2020). In its representation of protagonist Sam Winchester’s eating disorder, Brittle engages with the dominant cultural narratives associating disordered eating with a desire for control and with femininity. This case study illustrates how fanfiction can explore complex emotional tensions that remain underexplored on mainstream TV while simultaneously undermining cultural taboos and stereotypes regarding mental illness.